Enhanced heat transfer and symmetry breaking in three-dimensional electro-thermo-hydrodynamic convection. (June 2023) - Wang, Qi; Guan, Yifei; Wu, Jian
In this work, the electro-thermo-hydrodynamic convection system induced by unipolar charge injection between two parallel electrodes is numerically investigated. A two-relaxation-time lattice Boltzmann method coupled with a fast Poisson solver is implemented to obtain the temporal and spatial distributions of the flow field, temperature field, electric field, and charge density of the system. Due to the electric force and destabilizing buoyancy force, the system exhibits electro-thermo-convective vortices and transitions to a chaotic flow field, where the flow fluctuates irregularly in time. The strong electric driving force is shown to double the heat transfer effects measured by the Nusselt number ( Nu ). The size of the computational domain is found to influence the stability and flow analysis. Specifically, the system is chaotic in a large computational domain but the same set of parameters can lead to a steady-state condition in a small domain.